Bureaucratic Corruption, Democracy and Judicial Independence (Asian Business Research, 2016)
The theoretical literature in economics and political science has made numerous efforts in understanding the determinants of corruption and stressed the importance of political institutions in shaping the patterns of government corruption. Nevertheless, very few researches focus on the role of judicial system. Employing a formal model with empirical analyses, I incorporate economic factors with political constraints to investigate the different roles of democracy and judicial independence in determining the level of bureaucrats’ corruption across countries. Empirically, the instrumental variable (IV) approach is applied to resolve the endogeneity problems. The evidence indicates that different levels of corruption across countries are significantly influenced by the degrees of judicial independence. To fight corruption successfully, I contend that the judiciary, as a hard institutional constraint to resist bureaucratic corruption, has to be independent from the government.